Diabetic patient assessment of chronic illness care using PACIC+ - Malliarou, Maria; Desikou, Christina; Lahana, Eleni; Kotrotsiou, Styliani; Paralikas, Theodosios; Nikolentzos, Athanasios; Kotrotsiou, Evangelia; Sarafis, Pavlos (My University, 2020)
The Patient Assessment of Chronic Illness Care plus is used in order to assess whether provided care is congruent with the Chronic Care Model, according to patients. The purpose of this study was to correlate PACIC+ and the revised 5As "ask, advise, agree, assist and arrange" scoring of a sample of DM patients, with their QoL, depressive symptomatology, demographic and disease characteristics, self-management behaviours of healthy eating and physical activity.
Keywords: CES-D; Chronic care model; Chronic illness; Diabetes; Quality of life; SF-36